Gas-chromatographic measurements of atmospheric methane at Syowa Station between February 1986 and January 1987 - Hirota, Michio; Fukabori, Masashi; Yamanouchi, Takashi; Makino, Yukio (National Institute of Polar Research, 1989)
P(論文) Atmospheric methane (CH_4) was measured by a gas-chromatographic method. Air samples were collected at Syowa Station between February 1986 and January 1987. The mean volume mixing ratio in this period was 1.613 ppm. An increasing trend for mixing ratios of CH_4 including those in 1983 was 1.1%/year as of January 1987. departmental bulletin paper